Optimal chemokine receptors for enhancing immune cell trafficking in adoptive cell therapy - DoYeon Han; Byung-Kwan Jeong; Jong Moo Hong; Jeong-Han Seo; GunHee Lee; Kwanghee Kim; Chorong Hong; Hyeonjin Lee; Su Min Cha; Jong Hyeok Kim; Taehyun Park; Gyungyub Gong; et al. (Immunologic Research, 2025)

Genetic characterization of a locus responsible for low pungency using EMS-induced mutants in Capsicum annuum L. - Seungki Back; Jung-Min Kim; Hayoung Choi; Joung-Ho Lee; Koeun Han; Doyeon Hwang; Jin-Kyung Kwon; Byoung-Cheorl Kang (Theoretical and Applied Genetics, 2024)
Key message The pepper mutants (‘221-2-1a’ and ‘1559-1-2h’) with very low pungency were genetically characterized. The Pun4 locus, responsible for the reduced pungency of the mutant fruits, was localized to a 208 Mb region on chromosome 6. DEMF06G16460, encoding 3-ketoacyl-CoA synthase, was proposed as a strong candidate gene based on the genetic analyses of bulked segregants, DEG, and expression analyses. Abstract Capsaicinoids are unique alkaloids present in pepper ( Capsicum spp.), synthesized through the condensation of by-products from the phenylpropanoid and branched-chain fatty acid pathways, and accumulating in the placenta. In this study, we characterized two allelic ethyl methanesulfonate-induced mutant lines with extremely low pungency (‘221-2-1a’ and ‘1559-1-2h′). These mutants, derived from the pungent Korean landrace 'Yuwolcho,' exhibited lower capsaicinoid content than Yuwolcho but still contained a small amount of capsaicinoid with functional capsaicinoid biosynthetic genes. Genetic crosses between the mutants and Yuwolcho or pungent lines indicated that a single recessive mutation was responsible for the low-pungency phenotype of mutant 221-2-1a; we named the causal locus Pungency 4 ( Pun4 ). To identify Pun4 , we combined genome-wide polymorphism analysis and transcriptome analysis with bulked-segregant analysis. We narrowed down the location of Pun4 to a 208-Mb region on chromosome 6 containing five candidate genes, of which DEMF06G16460 , encoding a 3-ketoacyl-CoA synthase associated with branched-chain fatty acid biosynthesis, is the most likely candidate for Pun4 . The expression of capsaicinoid biosynthetic genes in placental tissues in Yuwolcho and the mutant was consistent with the branched-chain fatty acid pathway playing a pivotal role in the lower pungency observed in the mutant. We also obtained a list of differentially expressed genes in placental tissues between the mutant and Yuwolcho, from which we selected candidate genes using gene co-expression analysis. In summary, we characterized the capsaicinoid biosynthesis-related locus Pun4 through integrated of genetic, genomic, and transcriptome analyses. These findings will contribute to our understanding of capsaicinoid biosynthesis in pepper.

Utilizing waste carbon residue from spent lithium-ion batteries as an adsorbent for CO2 capture: A recycling perspective - Yu-Ri Lee; A. Ra Cho; Seongmin Kim; Rina Kim; Shuang Wang; Yosep Han; Hyungseok Nam; Doyeon Lee (Chemical Engineering Journal, 2023)

Multipurpose advanced split T7 promoter-based transcription amplification for ultrasensitive molecular diagnostics - Jiye Shin; Taehwi Yoon; Daehan Nam; Doyeon Kim; Seokjoon Kim; Byung Seok Cha; Eun Sung Lee; Youngjun Jang; Seokhwan Kim; Jinjoo Han; Hyun-Jung Choi; Ki Soo Park (Chemical Engineering Journal, 2023)